Variations of arbuscular mycorrhizal fungi following succession stages in a tropical lowland rainforest ecosystem of South China - Yang, Huai; Mai, Siwei; Liu, Wenjie; Fu, Jialin; Yang, Qiu; Zhang, Bin; Huang, Biao (Frontiers in Ecology and Evolution, 2023)
Introduction The grasslands in the Nature Reserve of Ganshenling, in the south of Hainan Island, were first formed after deforestation disturbance before a natural restoration of shrubs and secondary forests. However, the stages of grassland and shrubs in some parts of Ganshenling regions could not be naturally restored to secondary forests. In addition, the forest form of the secondary forest after 40 years (40a) of succession was similar to that of the secondary forest of 60 years (60a). However, it was not known whether the microorganisms recovered to the level of the secondary forest of 60a. Arbuscular mycorrhizal fungi (AMF) are plant root symbionts that can improve the nitrogen and phosphorus absorption of plants and play a key role in secondary forest succession. An understanding of the essential role of soil AMF in secondary forest succession of tropical rainforest in Ganshenling regions is still limited. Methods Therefore, the soil of 0–10 cm was collected with the help of a 5-point sampling method in grassland, shrubs, and second tropical lowland rainforest of 40a and 60a. We studied community changes in AMF with the succession and explored the impacts of soil physicochemical properties on soil AMF. Results Our findings were as follows: (1) Different successional stages showed divergent effects on soil AMF communities. (2) After 40a recovery, the alpha-diversity indices of AMF recovered to the level of secondary forest of 60a, but the similarity of soil AMF communities only recovered to 25.3%. (3) Species richness of common species, rare species, and all the species of AMF showed a significantly positive correlation with soil nitrogen. (4) OTU10; OTU6, OTU9, and OTU141; OTU3 and OTU38; and OTU2, OTU15, OTU23, and OTU197 were significantly unique AMF for grasslands, shrubs, and secondary forests of 40a and 60a, respectively. (5) The phylogenetic tree and the heatmap of AMF showed that the OTUs in grasslands and shrubs were in contrast to the OTUs in secondary forests of 40a and 60a. Discussion We concluded that the succession of a secondary forest after deforestation disturbance was probably limited by its AMF community.